OPTIMALISASI SUMBER DAYA MANUSIA DI DESA MANGKIT DENGAN BENTUK IMPLEMENTASI MEDIA POJOK LITERASI: Optimization of Human Resources in Mangkit Village by Implementation of Literacy Corner Media - Embong Bulan, Cristhina; Pesak, Geraldy; Kalangi, Paulus; Nitami, Chantika; Ngala, Enjel; Wawo, Rohelio; Johanis, Alya; Salsabila, Syifa; Nina, Vinda; Donsu, Chrisviana; Reosunaung, Esterlita; Salaki, Deiby (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
The Student Organization Capacity Building Program (PPK-ORMAWA) conducted by the Himmatika team from Sam Ratulangi University aimed to enhance students' capacity for community service in Mangkit Village, Minahasa Tenggara, North Sulawesi. The program aimed to identify and address critical issues such as statistical literacy, student interests and talents, health, investment, and technology by establishing five literacy corners: Statistics Porch, Creative Zone, Medical Corner, Innovative Investment, and Technology Corner. The program involved planning, implementation, and monitoring, involving coordination with village officials, community leaders, and relevant partners. Related outreach and training were also conducted to improve community literacy and skills. Program monitoring and evaluation were carried out regularly to ensure the program's effectiveness and success, as well as to make improvements based on feedback. The results of this program were the establishment of five literacy corners that can support the improvement of literacy in Mangkit Village, with the literacy corners serving as learning centers that encourage active participation from various age groups. Through these programs, the team successfully achieved its goals of strengthening the capacity of the Mangkit Village community, making a positive impact on the literacy, health, and economy of the local community, and contributing to the development of a smarter and more competitive village. ABSTRAK Program Penguatan Kapasitas Organisasi Mahasiswa (PPK-Ormawa) oleh tim Himmatika Universitas Sam Ratulangi bertujuan memperkuat kapasitas mahasiswa dalam pengabdian masyarakat di Desa Mangkit, Minahasa Tenggara, Sulawesi Utara. Tujuan program ini adalah mengidentifikasi dan mengatasi isu-isu penting seperti literasi statistik, minat dan bakat siswa, kesehatan, investasi, dan teknologi melalui pendirian lima pojok literasi: Serambi Statistika, Zona Kreatif, Sudut Medika, Investasi Inovatif, dan Teknologika. Program ini melibatkan perencanaan, pelaksanaan, dan monitoring, dengan pendekatan yang melibatkan koordinasi dengan pejabat desa, tokoh masyarakat, serta mitra terkait. Penyuluhan dan pelatihan terkait juga dilakukan untuk meningkatkan literasi dan keterampilan masyarakat. Monitoring dan evaluasi program dilakukan secara berkala untuk memastikan efektivitas dan keberhasilan program, serta melakukan perbaikan berdasarkan umpan balik. Hasil dari program ini adalah dihasilkannya lima pojok literasi yang dapat membantu menunjang peningkatan literasi di Desa Mangkit, dengan pojok literasi menjadi pusat belajar yang mendorong partisipasi aktif dari berbagai kelompok usia. Melalui program-program ini, tim berhasil mencapai tujuan dalam penguatan kapasitas masyarakat Desa Mangkit, membawa dampak positif dalam literasi, kesehatan, dan ekonomi masyarakat setempat, serta berkontribusi terhadap pembangunan desa untuk mewujudkan desa cerdas dan berdaya saing.